Simbología religiosa y conflictos sociales en el sur andino - Urbano, Henrique Osvaldo (1974)
Neither the movement to "extirpate idolatry" in the 16th and 17th centuries, nor the ecclesiastical structure and apparatus that has prevailed in the Andes since the dawn of the 17th century, have been sufficient to eliminate rites, beliefs and myths that still constitute the background of the Andean religious discourse. The existence of a religious system specific to the Andean area is significant because the spread and imposition of Christianity was one of the constant concerns of conquerors and missionaries, Creoles and Republicans. How to explain the validity of ancient rites and symbolic expressions of their own if not for the fact that one and the other are fundamental for the existence of a people that is master of its own destiny?